Primeira Ata de 08/12/1975, da primeira reunião da Comissão de Pós-Graduação Coordenadora do PPGE/UFSCar (First Minutes of the first meeting of the Postgraduate Committee Coordinator of the PPGE/UFSCar on 12/8/1975) - Revista Eletrônica de Educação, Reveduc - (Revista Eletrônica de Educação, 2017)
Primeira Ata de 08/12/1975, da primeira reunião da Comissão de Pós-Graduação Coordenadora do PPGE/UFSCar. (First Minutes of the first meeting of the Postgraduate Committee Coordinator of the PPGE / UFSCar on 12/08/1975)